ENT 530 Social Media Portfolio: Chelum Sarawak Chocolate / Muhammad Fikri Md Yazid - Md Yazid, Muhammad Fikri (2021)
Suke.manis is a pastry and dessert specialises in cheese and chocolate. Suke.manis was founded by a University student who runs a business in his spare time. Suke.manis now offers two types of desserts wjich is fruit pudding and cheese cake. Oreo, chocolate chips, chipsmore, nutella, m&m, and kinder bueno are the five flavour choices for cheese cake. This product has become more popular, particularly in Jelebu, Negeri Sembilan. It is also one of the efforts to promote Suke.manis by completing the assignment. I've been in charge of social media accounts such as Facebook and Instagram. Because of the Covid 19 epidemics, this portfolio would be a great promotion for Suke. Manis works on a "Cast On Delivery" basis as well.